Acoustic Fields to Levitate Big Water Drops - Gaete-Garreton, L; Vargas-Hernandez, y; Meneses-Díaz, J; Cancino-Jaque, E (Institute of Physics, 2024)
In this report, we described the main characteristics of acoustic fields allowing the levitation of big water drops. A numerical study is presented for different configurations of levitators and their associated acoustic fields. It is shown that an emitter different to a piston-type source, for instance, a circular plate excited in its center, vibrating at its first axisymmetric eigenmode can produce an acoustic field with improved levitation capabilities. © 2024 Institute of Physics Publishing. All rights reserved.